1995
DOI: 10.1002/ajim.4700270608
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and lung function in wool textile workers

Abstract: Our study investigated a group of 216 wool textile workers (158 women and 58 men). Respiratory symptoms were assessed by questionnaire in wool textile workers and in 130 not exposed (control) workers. Ventilatory capacity was measured in wool workers by recording maximum expiratory flow-volume (MEFV) curves on Monday before and after the work shift. Forced vital capacity (FVC), 1-second forced expiratory volume (FEV1), and flow rates at 50% and the last 25% of the vital capacity (FEF50, FEF25) were measured on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…The prevalence of occupational asthma in female tobacco workers (7.2%) was similar to that reported in other occupational groups exposed to organic dusts associated with airway disease such as textile workers [Zuskin et al, 1990[Zuskin et al, , 1996 and food processing workers [Zuskin et al, 1988a[Zuskin et al, ,b, 1992. Huuskonen et al [1984] suggested that exposure to spores of different molds in the manufacture of tobacco products may induce symptoms and signs relating to extrinsic allergic alveolitis.…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence of occupational asthma in female tobacco workers (7.2%) was similar to that reported in other occupational groups exposed to organic dusts associated with airway disease such as textile workers [Zuskin et al, 1990[Zuskin et al, , 1996 and food processing workers [Zuskin et al, 1988a[Zuskin et al, ,b, 1992. Huuskonen et al [1984] suggested that exposure to spores of different molds in the manufacture of tobacco products may induce symptoms and signs relating to extrinsic allergic alveolitis.…”
Section: Discussionsupporting
confidence: 78%
“…The results therefore resemble our results in this area. The effect of occupational exposure to dust, fumes, and gasses on the prevalence of rhinosinusitis has been addressed by others by comparing prevalence of rhinosinusitis in traditional “high exposure” occupations such as spice factory workers [Zuskin et al, 1988], paper‐recycling workers [Zuskin et al, 1998], cement factory workers [Al‐Neaimi et al, 2001] and wool textile workers [Zuskin et al, 1995] to the rhinosinusitis prevalence in “low exposure” occupations such as fruit‐bottling workers, packers in food industry, health examiners and delivery workers, respectively. Results of this comparison revealed, in accordance with our findings, significantly higher rhinosinusitis prevalence among “high exposure” workers.…”
Section: Discussionmentioning
confidence: 99%
“…Other than musculo-skeletal problems, there is also a risk of development of chronic respiratory symptoms and impaired lung function. [5] Also studies are rare with respect to respiratory problems in women in spinning section of the woolen industry, hence the need was felt to investigate the respiratory functions in women working in such type of unit.…”
Section: Introductionmentioning
confidence: 99%